Educating children with facial disfigurement : creating inclusive school communities - Frances, Jane (London ; New York : RoutledgeFalmer ; Taylor & Francis Group, 2004)
Children and young people who are visibly different face significant social and psychological challenges at school. Educating Children with Facial Disfigurement demystifies a difficult and delicate subject. Teachers and others working in education can use this book to acquire a better knowledge of the issues involved, as well as the confidence to handle sensitive issues and foster inclusive attitudes both in and out of the classroom. There are many causes of facial disfigurement - birthmarks, cleft lip and palate, burns, scars and serious skin conditions - so it is essential that all schools know about the issues arising from visible difference. Jane Francis examines many of these issues and demonstrates in a practical way how to deal with: staring, curiosity and questions, teasing, name-calling and bullying, medical needs, special educational needs and related issues, creating inclusive school communities, self-perception and self-expression and career ideas, work experience and social skills for life. With illustrative case studies, lesson ideas and references to useful resources, this book will be of particular relevance to teachers with responsibility for special educational needs or pastoral care.
1. Our beliefs and feelings about disfigurement -- 2. Having something to say -- 3. A new pupil or a pupil returning from hospital -- 4. Creating inclusive school communities -- 5. Teasing, name-calling, ostracism, and bullying -- 6. Self-esteem -- 7. Social skills for life -- 8.Self-perception and self-expression -- 9. Looking anew at a pupil's situation -- 10. Thinking about careers -- 11. Medical needs, special educational needs and related issues.
Includes bibliographical references.
Keywords: FACE -- ABNORMALITIES